Time Course of Performance Fatigability during Exercise below, at, and above the Critical Intensity in Females and Males. Issue 10 (12th October 2022) - AZEVEDO, RAFAEL DE ALMEIDA; FOROT, JONAS; IANNETTA, DANILO; ABOODARDA, SAIED JALAL; MILLET, GUILLAUME Y.; MURIAS, JUAN M.
ABSTRACT: Purpose: This study aimed to investigate the time course and amplitude of performance fatigability during cycling at intensities around the maximal lactate steady state (MLSS) until task failure (TTF). Methods: Ten females and 11 males were evaluated in eight visits: 1) ramp incremental test; 2–3) 30-min constant power output (PO) cycling for MLSS determination; and 4–8) cycling to TTF at PO relative to the MLSS of (i) −15%, (ii) −10 W, (iii) at MLSS, and (iv) +10 W, and (v) +15%. Performance fatigability was characterized by femoral nerve electrical stimulation of knee extensors at baseline; minutes 5, 10, 20, and 30; and TTF. Oxygen uptake, blood lactate concentration, muscle oxygen saturation, and perceived exertion were evaluated. Results: Approximately 75% of the total performance fatigability occurred within 5 min of exercise, independently of exercise intensity, followed by a further change at minute 30. Contractile function declined more in males than females (all P < 0.05). At task failure, exercise duration declined from MLSS−15% to MLSS+15% (all P < 0.05), accompanied by a greater rate of decline after MLSS+15% and MLSS+10 compared with MLSS, MLSS−10, and MLSS−15% for voluntary activation (−0.005 and −0.003 vs −0.002, −0.001 and −0.001%·min −1, respectively) and contractile function (potentiated single twitch force, −0.013 and −0.009 vs −0.006, −0.004 and −0.004%·min −1, respectively). Conclusions: Whereas the time course of performance fatigability responses was similar regardless of exercise intensity and sex, the total amplitude and rate of change were affected by the distinct metabolic disturbances around the MLSS, leading to different performance fatigability etiologies at task failure.